Egyptian mothers’ preferences regarding how physicians break bad news about their child’s disability: A structured verbal questionnaire - Abdelmoktader, Ahmed Mahmoud (BioMed Central, 2012)
BACKGROUND: Breaking bad news to mothers whose children has disability is an important role of physicians. There has been considerable speculation about the inevitability of parental dissatisfaction with how they are informed of their child’s disability. Egyptian mothers’ preferences for how to be told the bad news about their child’s disability has not been investigated adequately. The objective of this study was to elicit Egyptian mothers’ preferences for how to be told the bad news about their child’s disability. METHODS: Mothers of 100 infants recently diagnosed with Down syndrome were interviewed regarding their preferences for how to be told bad news. Mothers were recruited through outpatient clinics of the Pediatric Genetics Department at Fayoum University Hospital (located 90 km southwest of Cairo, Egypt) from January to June 2011. RESULTS AND DISCUSSION: Questionnaire analyses revealed nine themes of parental preferences for how to be told information difficult to hear. Mothers affirmed previously reported recommendations for conveying bad medical news to parents, including being told early, being told of others with a similar condition, and being informed of the prognosis. CONCLUSIONS: Mothers affirmed communication themes previously discussed in the literature, such as being told early, and being informed of the prognosis. Although more research is needed in this important area, we hope that our findings will stimulate future search and help health care providers in different societies establish guidelines for effectively communicating bad news.